Die Familie als Ort der Erziehung des Menschen. Eine Skizze zur "Metaphysik des Muttertums" Wilhelm Schapps - Nowikow, Igor (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2011)
Wilhelm Schapp, the German philosopher (a student of Edmund Husserl), wrote his treatise “Zur Metaphysik des Muttertums” in 1937, but the book was not published until 1965, fourteen days before the author’s death. Its theme is motherhood and family. This article attempts to interpret the Wilhelm Schapp`s text; the subject of the analysis is, firstly, the meaning of the title phrase “Metaphysik des Muttertums” (“metaphysics of motherhood”), and secondly, the role of the family in the educational process. In his metaphysical work Wilhelm Schapp appears as a philosopher, strongly connected with the Christian tradition; according to him the main term of this tradition is not reason, but love, the deepest manifestation of which is motherhood.
Keywords: Husserl; Christian tradition